PENGARUH SUKU BUNGA DAN PENDAPATAN PERKAPITA TERHADAP TABUNGAN DI KABUPATEN BANYUMAS - Mohammad Hidayatul Holili; Sri Heneng Prasastono (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The Research that entitled “The Influence of Interest Rate and Earnings Percapita To Saving In Banyumas Regency”. Data that used are secondary data : interest rate of deposit at public bank, GDRB according to Constant price in Banyumas Regency, sum up resident in Banyumas Regency, saving of Banyumas sociedy, period of year time are 2016-2021 aims to 1) partial analyzing the influence of interest rate an earning per capita to saving in Banyumas Regency (2) knowing the most factor effects to saving in Banyumas Regency. The Result of analyzing during period 2016-2021 shows : Saving mean in Banyumas Regency during the research period are Rp. 1.634,683 milliar, the mean of interest rate are 19,50%. The mean of Earnings percapita during the research period are Rp. 1.498.677,- its better than minimum regional wage, it’s mentioned indicate that the good enough society Banyumas earnings. The correlation coefficient show that the variable of interest rate has a strong relation with saving, its mentioned of 0,596, The correlation coefficient of earnings percapita with saving are 0,943. It’s mean that retation of variable of earnings percapita has the strong relation with saving. Partial effects from independent variable show that interest rate and earnings percapita have a significant effect. Earnings percapita is a most effect to saving its show by significance of alpha 0,000 and t value is 6,951 its above of t tables 2,18 interest rate has t value 3,238 with the significance of alpha 0,017. Simultan effects show that independent variable (interest rate and earnings percapita) have an effect to saving with significance of alpha 5%, it’s mentioned proved with the F value 40,259 bigger than F tables 3,86 and with significances of alpha 0,000. Based on elasticity of earnings percapita have a biggest effect to saving with the value 1,314. Therefore, government of Banyumas Regency suggested to make-up of earnings percapita so that saving in Banyumas Regency can increase.